Human Resource Practice in Nigeria: Examination of Post-Covid ERA - John Mark (Research Parks Publishers, 2022)
The paper adopted mean and standard deviation in the evaluation of human resource practice in the post COVID era, having used SPSS as analytical tool in the interpretation of data. The research surveyed three major banks in Obio/Akpor local government area of Rivers State, thus: Sterling bank, Access bank and GTB bank. The paper claims that the on-line trade system which is the dream of the capitalist states is fast clamping down on the African market for one, based on a survey done on three selected banks in Obia/Akpor municipality, it was observed that most of the companies took to the on-line trade system, having laid off some of their workers and some placed on the admin desk to report from their homes. The consequence of this is that the human resource practice is being challenged by the new media which in many ways helps the bank to reduce bank crowding and maintain social distance. In other words, while bank crowding is on the slide through the use of the ATM machine and the cyber space, the activities of the human resource personnel would rarely be needed. The paper recommends that while the traditional human resource practice is on the challenge, the best may be for personnel to sell their service to the online train.